Near-Field Inductive Coupling Induced Polarization Control in Metasurfaces - Cong, Longqing (2017)
Inductive coupling of the identical bianisotropic meta-atoms is demonstrated to be dependent on the spatial distance. Here, a nonintuitive orientation-dependent switchable coupling phenomenon is experimentally studied and the applications in polarization control of the proposed metasurface are shown.